KURIAKOSE ELIAS CHAVARA IN THE FORMATION OF HUMAN CAPITAL AND ITS IMPACT ON INDIAN SOCIETY - Thomas, Deepa; Thomas, Kennedy Andrew (Journal of Dharma, 2020)
Developing knowledge societies encompasses personal, social, ethical and political dimensions, integrating all its members and promoting new forms of solidarity involving both present and future generations. Kuriakose Elias Chavara had realized the power of human capital formation for the integral development of the society and initiated pioneering efforts to develop human capital, and established two indigenous religious congregations, Carmelites of Mary Immaculate (CMI) for men and Congregation of the Mother of Carmel (CMC) for women. The objective of this paper is to synthesize the vision of Kuriakose Elias Chavara regarding the concept of human capital formation and examine its result based on vision actualization of CMC congregation and its members and institutions. The paper is divided into three sections; the first section discusses the meaning of human capital formation in the Kerala and Indian context. The second section deals with the human capital formation through the vision and mission of Chavara and the last section explains the human capital formation and women empowerment, and its impact on knowledge societies through CMC congregation. It explains the transformation of individuals inspired by the vision of founder and support of the Congregation, which brings tremendous changes in the society.